The Anatomy of the Sigmoid-Transverse Junction According to the Tentorial Angle. Issue 7 (October 2019) - Vatansever, Alper; Mut, Melike; Ergun, K. Mine; Oğuz, Kader Karli; Gümeler, Ekim; Bulut, Elif; Tatar, Ilkan
Abstract : Abstract: Dural sinuses have critical importance during intracranial approaches. Detailed anatomical knowledge of the dural sinuses is crucial for surgeons to reduce unexpected venous bleeding. The aim of this study was to investigate anatomical relation of sigmoid sinus and tentorium cerebelli according to clinically palpable landmarks and cranial morphometry. The authors evaluated 222 individuals' (94 women, 128 men) 3-dimensional computed tomography angiograms, retrospectively. The authors also studied on 12 mid-sagittal cut dried hemiskulls and 8 formalin fixed cadaver heads hemisected midsagitally. All measurements were completed using Osirix-Lite version 9 software. Craniometrical values were measured to define cranium morphology. Furthermore, level of the sigmoid sinus according to asterion and tentorial angle were evaluated in detail. Our results demonstrated that there were significant differences between parameters and genders, except vertical angle of the tentorium cerebelli. Distance between asterion and sigmoid sinus was statistically different between right and left sides in favor of the left side. This also varied depending on the position of the sigmoid sinus, as well. Only transverse angle between the upper point of external acoustic meatus and asterion demonstrated a significant correlation with age. This study evaluated the detailed 3D anatomy of sigmoid sinus and tentorium cerebelli related with the cranium morphology. Determining to sigmoid sinus anatomy according to clinically palpable landmarks has advantages for setting surgical protocols and reducing to unexpected injuries while surgery to these structures. Abstract : Supplemental Digital Content is available in the text